2017
DOI: 10.4149/av_2017_318
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Coxiella burnetii among domestic ruminants and horses in Poland

Abstract: Summary. -Coxiella burnetii is the causative agent of Q fever. The cases of the disease are recorded in various species, including domestic animals. The aim of this investigation was to estimate the seroprevalence of C. burnetii in ruminants including cattle, sheep, goats, and horses. Totally, 2082 serum samples from 936 goats, 933 cattle, 89 sheep, and 124 horses, including various horse breeds, were tested by ELISA or complement fixation test. The examination revealed that Polish horses are seronegative whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Similarly, a large-scale study in Northern Ireland of 5182 animals found a seroprevalence of 6.2% [25]. A serosurvey recently conducted in Poland revealed a seroprevalence of 4.18% [26]. In the Netherlands, just before the 2007-2011 epidemic, the highest level ever reported in apparently healthy animals (16%) was described [27].…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, a large-scale study in Northern Ireland of 5182 animals found a seroprevalence of 6.2% [25]. A serosurvey recently conducted in Poland revealed a seroprevalence of 4.18% [26]. In the Netherlands, just before the 2007-2011 epidemic, the highest level ever reported in apparently healthy animals (16%) was described [27].…”
Section: Discussionmentioning
confidence: 93%
“…Szymańska-Czerwińska et al, tested 2082 serum samples taken from 936 goats, 933 cattle, 89 sheep and 124 horses, including various horse breeds, and revealed that Polish horses were seronegative, while in the populations of cattle and small ruminants, seropositive animals were present. The percentage of seropositive cattle, goats and sheep was 4.18%, 6.3%, and 13.48%, respectively [10].…”
Section: Discussionmentioning
confidence: 96%
“…After several small epidemics, the largest one occurred in 1982 in Ulhówek, formerly Zamość Province that resulted in 1300 human cases. Thus, the surveillance, and control-Q fever in livestock is of particular importance (Szymańska-Czerwińska et al, 2017). The authors investi-gated the seroprevalence of C. burnetii in horses and ruminants including cattle, sheep, and goats in Poland.…”
mentioning
confidence: 99%